Terrorism in India as a Determinant of Terrorism in Pakistan - Ullah, Assad (Asian journal of criminology, 2018)
Terrorism in Pakistan springs from many factors such as, poverty, corruption, inequality, sham democracy, and low-level literacy; however, the effect of terrorism in India over terrorism in Pakistan remains unnoticed. This study explores the role of terrorism in India as a determinant of terrorism in Pakistan. This fangled determinant of terrorism in Pakistan forms the premise of our work. The Johansen cointegration analysis technique confirms the long-run relationship among terrorism in India and Pakistan and unemployment in Pakistan. Error correction model (ECM) resulted 55% of convergence annually. Besides, ECM verifies both short and long-run causalities. The VECM Granger and Modified Wald (MWALD) causality tests reveal that terrorism in India and unemployment in Pakistan Granger causes terrorism in Pakistan, but no reverse causality exists. The study concludes that both terrorism in India and unemployment in Pakistan results in terrorism in Pakistan. Coping with terrorism, Pakistan and India must revisit their respective roles; and simultaneously, Pakistan should address the unemployment problem—which facilitates recruitment for the terrorist organizations.